2021
DOI: 10.3390/ijms22147287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuropeptide Y in the Nucleus Accumbens

Abstract: Neuropeptide Y (NPY), an abundant peptide in the central nervous system, is expressed in neurons of various regions throughout the brain. The physiological and behavioral effects of NPY are mainly mediated through Y1, Y2, and Y5 receptor subtypes, which are expressed in regions regulating food intake, fear and anxiety, learning and memory, depression, and posttraumatic stress. In particular, the nucleus accumbens (NAc) has one of the highest NPY concentrations in the brain. In this review, we summarize the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…This mirrors studies that show that parvalbumin (PV) interneuron and SOM innervation is required for the survival of new abGCs (193,194). The NPY receptor is Gi/o coupled, and while the pathway that regulates neurogenesis is thought to proceed through the Y1 receptor subtype, there are also receptor subtypes 2-6 -however, 6 is rodent specific and a pseudogene in humans (195,196). A subtype of NPY interneuron called the neurogliaform cell contains en passant boutons that release GABA into the extracellular space which largely act on extrasynaptic GABAB receptors to maintain basal inhibition in the brain (18,197,198).…”
Section: Introductionmentioning
confidence: 54%
“…This mirrors studies that show that parvalbumin (PV) interneuron and SOM innervation is required for the survival of new abGCs (193,194). The NPY receptor is Gi/o coupled, and while the pathway that regulates neurogenesis is thought to proceed through the Y1 receptor subtype, there are also receptor subtypes 2-6 -however, 6 is rodent specific and a pseudogene in humans (195,196). A subtype of NPY interneuron called the neurogliaform cell contains en passant boutons that release GABA into the extracellular space which largely act on extrasynaptic GABAB receptors to maintain basal inhibition in the brain (18,197,198).…”
Section: Introductionmentioning
confidence: 54%
“…Van den Heuvel et al ( 20 ) found that NPY injections into the NAc of rats induce a specific preference for fat, but not sugar or standard chow in these rodents, an effect that is thought to be mediated by Y1 receptors on enkephalinergic neurons (reviewed in ref. 48 ). Pandit et al ( 49 ) measured the effects of NPY infusion into the lateral hypothalamus, NAc, and ventral tegmental area on the motivation for, and consumption of, sucrose.…”
Section: Discussionmentioning
confidence: 99%
“… 122 NPY is widely distributed in the nervous system and is particularly highly expressed in NAc and BLA. 170 Numerous studies have demonstrated that NPY levels are negatively correlated with anxiety, 171 which may be related to neuroprotective effects by promoting neurogenesis and neuroplasticity, 172 and decreasing amygdala excitability. 173 NPY has been reported to be involved in the neuroplastic protective effects of AEA, and inhibition of its expression antagonizes the effects of URB597 in suppressing PTSD behavior.…”
Section: Aea Hydrolase Faah Inhibitors In Treatment For Anxietymentioning
confidence: 99%